2015
DOI: 10.1039/c5ta02009c
|View full text |Cite
|
Sign up to set email alerts
|

N-doped carbon nanocages with high catalytic activity and durability for oxygen reduction

Abstract: N-doped carbon nanocages with high specific surface areas exhibited excellent activity and durability for oxygen reduction reaction in acidic electrolytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…This is probably because during the process of high-temperature pyrolysis, decomposition of NH 4 Cl produces NH 3 gas, which disperses into the glucose-derived porous carbon matrix to react with oxygen functionalities. 32 Thus, nitrogen was doped into glucose-derived porous carbon, resulting in formation of Fe/C–N hybrids. Similar strategies with NH 4 Cl as N doping sources have also been reported in previous works for the preparation of N-doped carbon materials.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is probably because during the process of high-temperature pyrolysis, decomposition of NH 4 Cl produces NH 3 gas, which disperses into the glucose-derived porous carbon matrix to react with oxygen functionalities. 32 Thus, nitrogen was doped into glucose-derived porous carbon, resulting in formation of Fe/C–N hybrids. Similar strategies with NH 4 Cl as N doping sources have also been reported in previous works for the preparation of N-doped carbon materials.…”
Section: Resultsmentioning
confidence: 99%
“…Similar strategies with NH 4 Cl as N doping sources have also been reported in previous works for the preparation of N-doped carbon materials. 32,33 The O 1s XPS spectrum of Fe/N–C-2 could be fitted into three peaks at binding energies of 530.3, 532.1, and 533.5 eV (Figure S4a, Supporting Information), which are assigned to Fe–O in Fe 3 O 4 , 34 C=O, and C–O, 35 respectively. The C 1s spectrum of Fe/N–C-2 is fitted into four peaks at binding energies of 284.6, 285.1, 286.1, and 289.1 eV (Figure S4b, Supporting Information), corresponding to C=C, C=N, C–O and C–N, and O–C=O bond, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure S1A (Supporting Information), the blue mixture was transformed into foam‐like carbon composite after heating treatment and scalable production of CoO@Co/N‐C up to 10 gram can be achieved at one time (Figure S1B, Supporting Information). There are some previously reports on the synthesis of porous nanostructures based on NH 4 Cl‐induced gas template, such as 3D porous graphene, carbon nanocages, and graphite carbon nitride . It is worth noting that the introduction of NH 4 Cl not only served as gas templates, but also afforded nitrogen doping simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Another group investigated the influence of different N sources on the types of N species formed in the catalyst and showed that N incorporation from glycine contributed to higher catalyst activity while NH 3 treatment etched the catalyst surface, giving higher surface area and improved access of O 2 to protected active sites. , The importance of pore accessibility within the surface of the catalyst was suggested by researchers using a composite of N-doped graphene and CNTs . Other recent papers also report the synthesis of other metal-free catalysts for the ORR. …”
Section: Pyrolyzed Nonprecious Metal Catalystsmentioning
confidence: 99%